A CREATIVE PROBLEM SOLVING (CPS) LEARNING MODEL: APPLICATION TO OPPORTUNITIES MATERIAL - Sukriyah, Dewi (JEDMA Jurnal Edukasi Matematika, 2024)
The research was conducted to describe the application of the Creative Problem Solving learning model on Opportunity Material. This type of research is quantitative descriptive research conducted without testing hypotheses. The data taken in the form of: the teacher's ability to manage learning, student activities during learning, student learning outcomes, and student responses to the CPS learning process. The research was conducted at Yapenas Gempol Junior High School, class VIII, totaling 37 students. The data collection instruments were observation sheets, learning outcomes tests, and response questionnaires. The results showed that the teacher's ability to implement the creative problem solving learning model was categorized as good with an observation value of 3.25. Student activity during the creative problem solving learning model is categorized as active because 29 students get an activity score of ≥ 75%. Students' learning outcomes after following the learning were categorized as complete by obtaining a score of 82.7%. Student responses to the creative problem solving learning model were categorized as positive because of 13 student response items, 11 items were categorized as very good and 2 items were categorized as good.